(3GdJLhjO dHZjI GdeRjOs - (3YHO GdQMef Hf YJjb Hf Nda GdUbdj GdbQTj, CHh GdbGSe, GdeYQha H` GHf GdaMGe,J (B516 (3g` s ((3HhRGf Hf SfbQ Hf YHO Gddg GdQhei s)
(3ChdgG (B:s
(3jHOC HaUd ESfGO QhGjI GdGOZGe s
(3BNQgG (B:s
(3aEfg Qhi Yf GdSfhSi GdJcHjQ ef Chd ShQI Cde fTQM Edi NGJeI GdfGS hdaXg Gddg GcHQ gPg LedI cGajI ai eYQhaI GdJcHjQ hUaJg faYc Gddg hGYGfc hLYd Pdc dhLgg GdcQje Je cJGH GdJLQjO dHZjI GdeQjO HYhf Gddg hJajbg s
(3GdfSNI HgG MhGTs
(3ai GdbQGAGJ GdSHYs
(3Ydjg ELGRI HbQGAI GdcGJH Ydi Ydj Hf YHO Gddg Hf CHj GdWjH GdMQGjRi GdeYQha HEHf GdaGQhbi s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs